The expanding party universe: patterns of partisan engagement in Australia and the United Kingdom - Gauja, Anika; Grömping, Max (Sage Publishing, 2020)
Although membership is declining, parties continue to perform roles central to democratic governance in modern societies. Given this seeming paradox, we suggest that partisan identification, in complementing studies of formal membership, is a promising way of assessing the strength of parties’ democratic linkage. Using data from an original survey of voters in Australia and the United Kingdom, we analyse the participatory and demographic profiles of party supporters. We show that there are significant differences between supporters and those not committed to any party, as well as between supporters based on the strength of their party identification, substantiating the idea that parties can be conceptualized as a series of concentric circles of increasing engagement but declining representativeness. Stronger supporters are more likely to engage with parties online, volunteer and donate, but are older, more likely to be male and less likely to be foreign-born. Our findings have important implications for democratic practice as parties seek to expand and rejuvenate their networks of affiliates.
In: Party Politics, 26 (2020), Nr. 6. pp. 822-833. ISSN 1354-0688 (Druck-Ausg.), 1460-3683 (Online-Ausg.)
Zweitveröffentlichung